What’s the "Deal" on Dented Canned Products: Are They Safe to Consume - Cheung, Tracie; BCIT School of Health Science, Environmental Health (BCIT Environmental Public Health Journal, 2010)
The following study was devised to determine whether dented cans should be sold in stores and if the refusal of dented cans from churches is a wise decision. The experimental procedures were set out to determine whether there is a significant difference in the proportions of contaminated cans to uncontaminated cans for two groups of dented cans and a group of non-dented cans. The pertaining legislation specifies to what extent a can should not be sold, however the extent of damage is usually at the discretion of an employee. Since the extent of damage could not be determined by the general public, this study looks at the type of damage. Two groups of dented cans were created to test if there is a difference in the likelihood of contamination between rim dents and body dents. A compression device was used to deliver a consistent force to each dented can. The forces at which the cans were subjected to were determined during a pilot study. The body and rim dented cans were subjected to 180 Newtons and 400 Newtons respectively. Two positive and two negative controls were made to test the microbiological component of this study. A total of 90 cans were tested for environmental organisms via the Pour Plate method. The results were statistically analyzed using the Chi-squared test. One out of 30 body dented cans showed the growth of microorganisms. In both the rim dented can group and the non-dented can group, no growth was found. The results of the study show that there is no association between dented and non-dented cans and the presence of environmental organisms as it reveals that the probability level of 0.363769 is greater than the set probability value of 0.05 and thus is not statistically significant.